P788 Endoscopic management of patients with high-risk colorectal colitis-associated neoplasia: a Delphi study. (30th January 2023) - Bak, M; Albéniz, E; East, J; Coelho-Prabhu, N; Suzuki, N; Saito, Y; Matsumoto, T; Banerjee, R; Kaminski, M; Kiesslich, R; Coron, E; de Vries, A; et al.
Abstract: Background: Current guidelines recommend endoscopic resection of visible and endoscopically resectable colorectal colitis-associated neoplasia (CAN) in patients with inflammatory bowel disease (IBD). However, patients with high risk CAN are often not amenable to conventional resections techniques and a consensus approach for the endoscopic management of these lesions is presently lacking. This Delphi study aims to reach consensus amongst experts on the endoscopic management of these lesions. Methods: A three-round modified Delphi process was conducted to reach consensus amongst worldwide IBD and/or endoscopy experts (n=18) from three continents. Experts were chosen based on the extensive clinical experience with IBD and/or EMR/ESD in patients with IBD, and the authorship on multiple peer-reviewed publications on CAN, the endoscopic resection of CAN and/or EMR/ESD. Consensus was considered if ≥ 75% agreed or disagreed. Quality of evidence was assessed by the criteria of the Cochrane Collaboration group. Results: Consensus was reached on all statements (n=14). Experts agreed on a definition for CAN and high-risk CAN (HR-CAN). Consensus was reached on the examination of the colon with enhanced endoscopic imaging prior to resection, the endoscopic resectability of a HR-CAN lesion and endoscopic assessment and standard report of CAN lesions. In addition, experts agreed on type of resections of HR-CAN (< 20mm, >20 mm, with or without good lifting), endoscopic success (technical success and outcomes), histologic assessment and follow-up in HR-CAN. Conclusion: This is the first step in developing international consensus-based recommendations for endoscopic management of (HR-)CAN. Although the quality of available evidence was considered low, consensus was reached on several aspects of the management of (HR-)CAN. The present work and proposed standardization might benefit future studies.